EP 94. Fecal incontinence treated by sacral neuromodulation: Worldwide largest single center study. Issue 9 (September 2016) - Janssen, P.; Melenhorst, J.; Breukink, S.; Temel, Y.
Abstract : Fecal incontinence (FI) is an embarrassing condition, which leads to social isolation. The first treatment option of FI is conservative therapy. If this fails, surgery is the next step. In the past, only invasive options like a colostomy were possible. In 1995 sacral neuromodulation (SNM) was introduced as a minimal invasive surgical therapy. The last 2 decades literature shows that it's a safe and effective option for treatment of FI. However, long outcome results of large patient cohorts with fecal incontinence treated by SNM are limited. This study shows the long term results of SNM for FI of a single high-volume center. All patients eligible for treatment of fecal incontinence with SNM between March 2000 and July 2015 were evaluated. Fecal incontinence was defined as involuntary fecal loss at least once per week. All patients underwent pre-operative work-up consisting of a defaecography, endo-anal ultrasound and a manometry. Besides they all filled in a 3 week bowel habit diary; objectifying decrease of involuntary fecal loss for the last 3 weeks, increase in time postponing defecation and decrease in defecation frequency. Post-operative follow-up was scheduled at 1, 3, 6 and 12 months after implantation and annually afterwards. Finally, all patients were asked to complete several quality of life questionnaires: Fecal Incontinence Quality of Life Score (FIQL), Short-Form 36 (SF-36) and the Vaizey-score. 374 patients were included (37 male) for a SNM screening-period after failing conservative treatment. In total, 334 (89.3%) patients received a permanent SNM. Mean age was 56.5 (17–82) years and mean follow-up was 85.1 months (3.0–183.4). Data showed a decrease in episodes of fecal loss per 3 weeks from 16.1 (3.0–107.0) at baseline to 3.0 (0.0–24.0) after SNM ( p < 0.001 ). Time postponing defecation increased from 1.48 min at baseline (0.0–30.0) to 7.5 (0.0–90.0) minutes after SNM implantation ( p < 0.001 ). Defecation frequency decreased from 2.7 at baseline (0.3–10.0) to 1.87 (0.3–6.0) defecations per day after SNM implantation ( p < 0.001 ). SNM was removed due to unsatisfactory results in 63 patients (16.8%). Quality of life evaluation using the SF-36 at different time points during follow-up was not significantly different from the general Dutch population. The FIQL demonstrated no changes in quality of life during follow-up between different follow-up moments. Mean Vaizey score was 11.47 (1.0–22.0). Major incontinence, defined as a Vaizey score of >6, was seen in 103 (79.2%) patients. This study shows long-term efficacy for SNM in the treatment of fecal incontinence with a stable reduction of episodes of fecal loss up to 10 years.